Revegetation of Tropical Peat Swamp Forest of Former Fires Using Local Tree Species in South Sumatra (Indonesia) - Bastoni Bastoni; Raissa Anjani; Andika Imanullah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Revegetation of tropical peat swamp forests (PSF) from former fires with local tree species has strategic value for the recovery of PSF, which has been largely lost and severely degraded by logging, conversion, drainage, and repetitive fires. The PSF recovery will be followed by increased forest cover, CO2 sequestration, O2 production, and peat ecosystem biodiversity. The method of revegetation that guarantees successful planting is still very lacking and has not been widely publicized. The study aimed to analyze the growth of revegetated plants on PSF of former fires. It used a field experiment design with four types of local peat plants, namely ramin (Gonystylus bancanus), punak (Tetramerista glabra), tembesu (Fragraea fragrans), and pulai (Alstonia pneumatophora). The results of the study showed that until the age of 2 years, the survival rate of revegetated plants ranged from 92.56%–94.69%, with growth of 32.53–44.94 cm/year and diameter growth of 0.87–1.21 cm/year. The growth of revegetated plants still accelerated in observations until the age of 3 years. This study provides optimism that PSF revegetation degraded by the fires could be carried out with satisfactory results.